Management of Facilities and Infrastructure in Improving the Quality of Learning - Rohmadi, Agung; Rahmat; Ardianto, Ardianto (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This study uses a type of qualitative research with a case study approach. The object of this research was carried out at SMK NU Losarang. Data collection techniques using observation, interviews and documentation. Data sources in this study included school principals, vice principals, subject teachers, TU staff and students, as well as other informants related to the problems raised in this study.The purpose of this study is to describe how the management of planning, procurement, evaluation and implications for facilities and infrastructure at SMK NU Losarang.The results of the study show that the management of facilities and infrastructure in improving the quality of learning at SMK NU Losarang consists of planning, procurement, use, and evaluation. (1) Planning for facilities and infrastructure at SMK NU Losarang is carried out in stages, starting with a needs analysis through data collection in the meeting forum of the teacher council and staff and employees. (2) Procurement of facilities and infrastructure at SMK NU Losarang is carried out in various ways. Facilities and infrastructure are obtained from the results of submitting assistance to various parties such as the government, the community, individuals and others. (3) Evaluation of the management of school infrastructure in improving the quality of learning is carried out by way of oral reports or written reports which are carried out on; (a) weekly evaluation; (b) monthly evaluation; and (c) annual evaluation. (4) The implications of the management of facilities and infrastructure at SMK NU Losarang are increasingly visible with the increasing quality of learning and student achievement.